2011
DOI: 10.4012/dmj.2010-102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of shear bond strengths of orthodontic brackets bonded with flowable composites

Abstract: This study evaluated the shear bond strengths of orthodontic brackets bonded to human premolars using five different combinations of flowable composites and one-step self-etching adhesives (n=12): (1) Adper Easy Bond+Filtek Supreme XT Flow; (2) Futurabond NR+Grandio Flow; (3) Clearfil S3 Bond+Clearfil Majesty Flow; (4) AdheSE One+Tetric EvoFlow; and (5) Transbond Plus Self Etching Primer+Transbond XT Light Cure Adhesive. After shear bond strength testing, adhesive remnant index (ARI) scores were given accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
1
8
1
3
Order By: Relevance
“…Easy handling is a highly desired characteristic because it reduces the working time of clinicians and chairside time of patients 19) . Various studies had shown that flowable composites exhibited comparable shear bond strengths as orthodontic adhesive Transbond XT and were promising materials for orthodontic bracket bonding 12,20,21) . Vertise Flow (Kerr, Orange, CA, USA) is a recently launched, self-adhesive flowable resin composite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Easy handling is a highly desired characteristic because it reduces the working time of clinicians and chairside time of patients 19) . Various studies had shown that flowable composites exhibited comparable shear bond strengths as orthodontic adhesive Transbond XT and were promising materials for orthodontic bracket bonding 12,20,21) . Vertise Flow (Kerr, Orange, CA, USA) is a recently launched, self-adhesive flowable resin composite.…”
Section: Introductionmentioning
confidence: 99%
“…However, with any kind of simplification in clinical application procedure, there arises a concern in loss of bonding 7) . During the last decade, numerous studies were carried out to investigate the efficiency, durability, and robustness of contemporary bonding agents by evaluating their shear bond strength or tensile bond strength 6,[10][11][12][13][14][15] . While most TSERs 11) , TSSEs 11) , and AASs 12) were found to be suitable for orthodontic use, flowable composites failed to provide sufficient bonding strength for bracket attachment 12,16) .…”
Section: Introductionmentioning
confidence: 99%
“…Filled restorative materials have been used as orthodontic adhesives [12,13]. The principal drawback of polymeric composite restorative materials remains their high polymerization shrinkage [14].…”
mentioning
confidence: 99%
“…En relación a los cementos estudiados, el Transbond TM XT es considerado como "gold standard" para la adhesión de brackets por autores como Durrani y col (11) y Turgut y col. (22) Sim embargo, presenta algunas desventajas como un alto costo y demanda mayor tiempo clínico, a diferencia del Orthocem que debido a su presentación monocomponente presenta un menor número de pasos clínicos.…”
Section: Discussionunclassified
“…Sin embargo, al comparar los dos tipos de cementos se pudo observar una diferencia significativa. Los autores Turgut y col (22) , afirman que la diferencia encontrada al comparar los dos cementos puede deberse a que las muestras que obtienen mayores valores de resistencia al cizallamiento obtienen menores valores en la puntuación ARI.…”
Section: Discussionunclassified